2022
DOI: 10.3390/nu14235006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dietary Inflammatory Index and Postpartum Depression in Exclusively Breastfeeding Women

Abstract: (1) Background: Research has shown that chronic inflammation can increase the risk of depression. The dietary inflammatory index (DII) is a novel measure of dietary inflammation, which has been used to investigate the relationship between diet and mental disorders in adults. However, little research has been conducted to establish an association between dietary inflammation (as measured by DII) and postpartum depression (PPD) in exclusively breastfeeding women. (2) Methods: In this cross-sectional study, 293 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Seven of these studies were conducted in healthy adults across the lifespan [ 19 , 20 , 23 , 24 , 26 , 30 , 33 ]. Studies that have been conducted mainly in young adults found null associations between sleep quality and the DII [ 19 , 26 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of these studies were conducted in healthy adults across the lifespan [ 19 , 20 , 23 , 24 , 26 , 30 , 33 ]. Studies that have been conducted mainly in young adults found null associations between sleep quality and the DII [ 19 , 26 , 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven of these studies were conducted in healthy adults across the lifespan [ 19 , 20 , 23 , 24 , 26 , 30 , 33 ]. Studies that have been conducted mainly in young adults found null associations between sleep quality and the DII [ 19 , 26 , 30 , 33 ]. However, in middle-aged adults, Wirth, Fekedulegn, et al (2022) [ 24 ] showed that more pro-inflammatory diets were correlated with higher improved subjective sleep quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… EPDS SEES BRUMS Correlations between: - PPD and BMI at 6 month postpartum (r = 0.468, p = 0.021) - PPD and household income at 6 months (r = −0.391, p = 0.065) and at 12 months (r = −0.154, p = 0.556) - PPD and SEES at six months: (r = 0.642, p < 0.001); 12 months (r = 0.679, p = 0.003) - PPD and BRUMS at six months: (r = 0.701, p < 0.001); 12 months postpartum: (r = 0.680, p = 0.004) - PPD and PSQI at 12 month postpartum: (r = 0.752, p < 0.001) Regression analysis identified factors such as household income and fatigue as the strongest predictors of PPD at six months postpartum. Hanshuang Zou 32 China Age (years): - <25 (14.3%) - 26–35 (78.8%) - 36–45 (6.9%) Sample size: 293 Cross-sectional study Two divisions: - Two groups: - PPD - Non-PPD - Three groups - Low dietary inflammatory index (Q1, DII<33.3%) - Intermediate DII (Q2, 33.3%<DII<66.7) - High DII (Q3, DII>66.7%) Evaluation of the dietary quality by assessing the DII (dietary inflammatory index) scores, exploring whether exclusive breastfeeding mothers’ diet contributes to an inflammatory environment in the body, which consequently affected the occurrence of depression EPDS Occupation level: - Employed: Non-PPD 36.1%, PPD 63.9%; - Unemployed: Non-PPD 47.1%, PPD 52.9%; p=0.069 (Chi-square test) Education levels: - Junior high school and below: Non-PPD 10%, PPD 90%; - Specialized degree: Non-PPD 33.3%, PPD 66.7%; - Bachelor’s degree: Non-PPD 46.0%, PPD 54.0%; - Postgraduate and above: Non-PPD 51.6%, PPD 48.4%; p=0.021 Number of children: - 1 child: Non-PPD 35.6%, PPD 64.4%; - 2 or more children: Non-PPD 46.9%; PPD 53.1%; p=0.054 When comparing sociodemographic factors between groups with and without postpartum depression it was found that women with a junior high school education or less, who had their first child, were the sole caregiver for the infant, and had low levels of social support, were more likely to suffer from PPD. Unemployed women and woman with better sleep quality, on the contrary, were less likely to suffer from depression.…”
Section: Resultsmentioning
confidence: 99%
“…These results support the idea that the degree of inflammation in the maternal diet could have an influence on her BM cytokine levels. The importance of mDII on maternal health is evidenced in a study in Chinese breastfeeding women showing that a shift from a pro-inflammatory to an anti-inflammatory diet lowered the risk of postpartum depression [70].…”
Section: Discussionmentioning
confidence: 99%